Meteorización experimental de los fragmentos de matriz y de los vidrios volcánicos. (2004)
Se elaboró un «Diseño experimental completamente al azar de efectos fijos y de arreglo factorial 32» con dos factores y tres niveles: Materiales [vidrio volcánico coloreado (VVC), vidrio volcánico incoloro (VVI) y fragmentos de matriz (FM)] y Reactivos [ácido húmico (AH), ácido oxálico (AO) y agua acidulada (AA)]. La solubilidad se evaluó a través de la medida de dos variables maestras: pH, conductividad eléctrica (CE) y tres variables de control: aluminio (Al), silicio (Si) y hierro (Fe). Los FM presentaron mayor superficie específica, mayor superficie de reacción, mayor número de rasgos de alteración superficial y produjeron mayores cantidades de iones de Al3+, Si4+ y Fe3+ (72%), seguido por los VVC (23%). En los tres materiales a medida que transcurrió el tiempo, los tres reactivos tuvieron efecto muy agresivo sobre las superficies, formas y bordes. En los FM se evidenciaron mayores marcas o rasgos de alteración, en los VVI sólo se manifestaron a partir del segundo ciclo y fueron, por lo general, leves. 90% de los datos se localizaron dentro del campo de estabilidad de la alofana/imogolita a pH entre 6.0-7.2 y actividad del H4SiO4 entre 10-3.2-10-4.8, Un 7% de los datos se localizaron en el campo de estabilidad de la haloisita cuando el pH disminuyó y la actividad del H4SiO4 aumentó; 3% lo hicieron en el de la gibsita, cuando disminuyó la actividad del H4SiO4. Esto significa que en todos los casos para los tres materiales están las condiciones dadas para que se forme imogolita (alofana/imogolita). AH fue el reactivo que más extrajo Al, luego lo hizo AO. En ninguna de las reacciones los sistemas alcanzaron el equilibrio. Los procesos de disolución estuvieron gobernados por reacciones de primer orden durante el primer ciclo y de segundo orden en el segundo y tercer ciclos. Palabras claves: Vidrio volcánico, fragmentos de matriz, meteorización experimental, disolución, Cordillera Central colombiana. ABSTRACT To study in the laboratory the physical meteorization and chemistry of the womb fragments and of the volcanic glasses belonging to the North area of the Colombian Central Mountain range it was the central objective of this investigation. For it was elaborated it a «I Design experimental totally at random of fixed effects and of factorial arrangement 32» that has two factors with three levels each one, this way: Materials [(glass volcanic colored (VVC), glass volcanic colorless (VVI) and matrix fragments (FM)] and Reagents [acid humic (AH), acid oxalic (AO) and it dilutes acid (AA)]. The solubility was evaluated through the measure of pH, electric conductivity and three control variables: aluminum, silicon and iron. FM present bigger surface specific, bigger reaction surface, bigger number of features of superficial alteration and they are those that bigger quantities of ions of Al3+, Si4+ and Fe3+ topk place (72%), continue to these the VVC (23%). In the three materials it is observed that as it lapses the time, the three reagents, they go having a very aggressive effect on the surfaces, forms and borders of these, such effects are measured by the type of marks or prints, the intensity and the abundance of them. In those FM is where bigger marks or alteration features were evidenced in VVI they were manifested starting from the second cycle and they were, in general, light. 90% of the data were located inside the field of stability from the allophane/imogolite to pH values among 6.0-7.2 and, to values of the activity of the H4SiO4 among 10-3.2-10-4.8. 7% of the data is located in the field of stability of the haloysite when the pH diminishes and the activity of the H4SiO4 increases and, 3% makes it in that of the gibbsite, when it diminishes the activity of the H4SiO4. This means that in all the cases the given conditions were for the three materials formed imogolite (alophane-imogolite). The AH is the reagent that more it extracts to the, then makes it the AO, AA. In none of the experimental reactions on the systems reach the balance. The processes of breakup were governed by reactions of first order, during the first cycle and of second order in the second and third cycle. Key words: Glass volcanic, womb fragments, experimental meteorization, dissolution, Colombian Central Mountain.